The relationship between self-reported risky driving and personality traits in different samples of drivers - Endriulaitienė, A.; Šeibokaitė, L.; Markšaitytė, R.; Žardeckaitė-Matulaitienė, K.; Pranckevičienė, A.; Stelmokienė, A. (Psichologija, 2013)
Researchers agree that risky driving is one of the most important contributors to traffic accidents, and it is influenced by personality traits. While past research has revealed contradictory findings as to the value of personality in different driving contexts, the prediction of self-reported risky driving using personality traits is complicated. The lack of consistent findings might be due to the underestimation of the drivers’ sample, type, or driving context. The present study aimed to analyse the relationships between Big Five personality traits and self-reported risky driving in four different samples of drivers. The volunteer participants of the study were 143 novice drivers (with the driving experience no longer than one year, 67 males and 76 females); 231 young drivers (130 males, 104 females); 239 experienced drivers (134 males, 149 females); 165 professional drivers (males). They completed the Driver Behavior Questionnaire (DBQ, Parker et al., 1995) that assessed two self-reported risky driving factors (driving errors and intentional violations) and the Big Five Inventory (BFI, Benet-Martinez and John, 1998) that measured the drivers’ extraversion, conscientiousness, neuroticism, agreeableness, and openness to experience. Also, data about age, gender, driving experience and exposure were gathered. The results indicated that young drivers were most prone to risky driving (both errors and violations), whereas professional drivers might be described by the safest self-reported driving style. The structural equation modeling revealed different relations between personality traits and risky driving taking into account a driver’s gender and group (novice, young, experienced, or professional). It was found that in all tested drivers’ samples personality traits might be the proximal predictors of driving errors or distal predictors of driving errors with the mediation of intentional violations. More frequent self-reported intentional violations significantly predicted more frequent driving errors (β ranged from 0.18 to 0.53). The results of the study revealed no significant associations between personality traits and risky driving among novice drivers. SEM revealed a consistent predictive power of extraversion (β ranged from 0.16 to 0.37) and conscientiousness (β ranged from 0.17 to 0.31) for different drivers’ risky driving. These traits predicted self-reported risky driving of young male drivers, experienced drivers, and professional drivers. The predictive power of neuroticism, agreeableness, and openness was inconsistent in different samples. The higher neuroticism of young drivers (β = 0.22; 0.28) and experienced female drivers (β = 0.27) predicted more frequent self-reported driving errors but did not predict the risky driving of experienced male drivers and professional drivers. Higher openness predicted less frequent violations among young male drivers (β = –0.18), but more frequent errors in professional drivers (β = 0.16). Higher agreeableness predicted significantly less frequent self-reported violations of young male drivers (β = –0.32) and less frequent errors of professional drivers (β = –0.29). The findings suggest that personality traits might be useful predictors of risky driving, but the driving context and multiple aspects of a driver’s personality simultaneously should be taken into account.
Keywords: Big Five personality traits; self-reported risky driving; novice, young, experienced and professional drivers